Les Français et les Bourbons restaurés face à la mer. L’appréhension du monde naval par les rois et la société française 1815-1830 - Gaëtan Obéissart (Nuova Antologia Militare, 2023)
Since their childhood, Louis XVIII and Charles X have been in contact with the naval world. Conscious that this contributes to the enhancement of the prestige of the crown and to the influence of France, the two monarchs support the men and the initiatives aimed at promoting the military navy, its history, its current events and its recovery, within a post-Napoleonic French society wondering about the place that military action should now occupy in the running of the country. Paradoxically, the military world, here naval, suffers from a bad image in a context of questioning of the place of the armies in the nation and the State. But at the same time, the naval world remains present in the minds of many French people, the arts and the cultural world taking part in this discussion, and continues to be one of the elements of national prestige, which is put forward and which we keep the memory of greatness of yesteryear.